Utilization of community health volunteers in identification of hypertension cases in Kajiado county, Kenya - Claris, Jessicar W.; Oyore, John P.; Ogweno, Gordon (International Journal Of Community Medicine And Public Health, 2024)
Background: Hypertension, despite being preventable and manageable contributes greatly to global morbidity and mortality. Community health volunteers (CHVs) provide various health services, however their utilization in hypertension identification has neither been explored nor emphasized. We aimed to determine the sociodemographic characteristics of CHVs and their knowledge level in hypertension identification in Kajiado county, Kenya. Methods: This was a cross-sectional study with a mixed- methods approach. Using multi-stage sampling, we recruited 226 CHVs who were active in the past 6 months and gave informed consent. Researcher administered questionnaires and key informant interviews were used for data collection. Data analysis was conducted using the statistical package of social science version 23 and content thematic analysis for quantitative and qualitative data respectively. Results: The likelihood of screening was higher among the middle age (41-50 years) (p=0.031). CHVs had poor knowledge (93.4%) and only 34.1% had attended a hypertension specific training. A strong statistical difference was found between ever-received hypertension training and knowledge level (p=0.000, 95% CI). The likelihood of screening was higher among those trained (p=0.005, 95% CI and those with knowledge of signs and symptoms (p<0.001, 95% CI). The odds of hypertension identification were 3.74 times higher among CHVs who knew hypertension signs and symptoms. Conclusions: Overall, CHVs had poor hypertension knowledge. The likelihood of hypertension identification was higher in CHVs with good knowledge of hypertension. Further studies should be conducted to assess the impact of CHVs utilization in hypertension on health outcomes.